Planificación microcurricular y la coherencia con el currículo por competencias en las instituciones educativas públicas de la ciudad de Loja, periodo 2022-2023 - Pintado Castillo, Maribel Janela (2023)
One of the fundamental elements for developing a class is the micro curricular plan; this instrument is elaborated and based on guidelines published by the Ministry of Education. This research aimed to determine the coherence between micro-curricular planning with the general curriculum, also the emphasis on communication, digital, mathematical, and socio-emotional skills in public educational institutions in Loja, Ecuador, in the ninth year of Basic General Education. The plans of nine public educational institutions were analyzed, and they were selected randomly among sixteen of them. The information collection instrument was a checklist. In addition to this analysis, a systematic documentary review was carried out, which allows us to work with triangular results. This process guides the research in a mixed approach of a transversal type and a descriptive scope. As a result of the documentary review, the experts emphasize that education by competences allows a comprehensive development of the student. On the other hand, the results showed that the Ninth-year plans of the public educational institutions of Loja are 72.55% in coherence with the ministerial guidelines published. To sum up, education by competencies is appropriate, public educational institutions of Loja are carrying out micro curricular planning with a good level of professionalism and based on ministerial documents. Keywords: curriculum, competence, micro-curricular planning, curriculum with emphasis on competencies.